Minat dan Hasil Belajar Matematika Siswa Dengan Menggunakan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray - Wanda, Sari Mulya; Isnaniah, Isnaniah (Department of Mathematics Education , University of Jember, 2023)
This study aims to determine the interest in learning mathematics of students who take part in the Two Stay Two Stray Cooperative Learning Model and whether the learning outcomes of students who take part in the Two Stay Two Stray Cooperative Learning Model are better than the results of students who take conventional learning in Class VIII MTsN 9 Padang Pariaman Academic Year 2022/2023. This type of research is pre-experimental with the research design The Static Group Comparison Design. The population in this study were all grade VIII students of MTsN 9 Padang Pariaman for the 2022/2023 academic year. The sampling was carried out randomly by first testing the normality, homogeneity and average similarity of the population data. The samples in this study were students of class VIII.2 as the experimental class and students of class VIII.3 as the control class. The results showed that students' interest in learning mathematics in class VIII MTsN 9 Padang Pariaman who took part in learning the Cooperative Type Two Stay Two Stray learning model was 76.99% with strong criteria. Students' mathematics learning outcomes were processed using the t-test at a significant level α = 0.05, the value of tcount > ttable was obtained, namely 3.42 > 1.68; whereas with Minitab Software obtained P-value <α, namely 0.001 <0.05, so that H0 was rejected and H1 was accepted. So, it can be concluded that the mathematics learning outcomes of students who take the Two Stay Two Stray Cooperative learning model are better than those who take conventional learning in class VIII MTsN 9 Padang Pariaman in the 2022/2023 Academic Year. Keyword : Interest in Learning, Learning Outcomes, Type Two Stay Two Stray Cooperative Learning Model